Degeneration of sweetpotato seed in Tanzania: can cleaned-up, virus-tested seed help? - Ogero, K. (Wageningen University & Research, 2022)
Viruses are a major constraint to sweetpotato production at the Lake Zone, Tanzania. They can cause yield losses either through current season infections or infections carried through vine cuttings recycled from season to season. The main yield limiting viruses are SPFMV and SPCSV which cause yield losses of up to 40% and more than 52% respectively. When they coinfect, SPCSV suppresses RNA silencing in the host plant and weakens its defense mechanism therefore leading to an increase in SPFMV titers and development of SPVD. Infection with SPVD has been reported to cause up to 100% yield losses. Use of clean virus-tested vines disseminated through a ‘formal’ decentralized system is among the proposed strategies to address this. However, clean seed can get re-infected once exposed in the field leading to degeneration over generations, therefore requiring replenishment. There is a need to understand more about virus interactions with the crop and the environment. This will enable researchers and farmers to know the pattern of degeneration of planting material in different localities, which control measures to use and when to purchase new planting material. Understanding variations in yields of clean planting material after several generations of field propagation defines how seed producers can economically sustain the supply of quality planting material. Several technologies have been developed to aid on-farm management of sweetpotato viruses during seed production. These include use of insect-proof net tunnels. However, their effectiveness and optimal management for effective protection against viruses need to be investigated. Successful adoption of clean seed also requires an understanding of social aspects of seed acquisition including dominant sources, prices, farmers’ knowledge on diseases and control measures, among others. The overall research question addressed in this thesis is how can cleaned-up, virus-tested seed be incorporated into smallholder farming systems to reduce degeneration in sweetpotato? This overall question led to the following specific questions: a) How does seed initially sourced from cleaned-up virus-tested plants perform in different agro-ecologies following several seasons of on-farm propagation? b) What are farmers’ experiences with and actions towards degeneration including seed sourcing strategies? c) Can insect-proof net tunnels limit virus re-infection of clean sweetpotato planting material? d) How does ratooning affect vine production in insect-proof net tunnels?